Extracellular polymeric substances and sludge solid/liquid separation under Moringa oleifera and chitosan conditioning: a review. Issue 1 (1st January 2017) - Faye, Marie Christine Amie Sene; Zhang, Yanrong; Yang, Jiakuan
ABSTRACT: For economic reasons and availability, there has been substantial interest in using natural organic polymers in sludge conditioning as alternative substances to replace inorganic conditioners in developing countries. Many investigations have been done on their efficiency regarding the enhancement of sludge dewaterability. Moringa oleifera seeds extract and chitosan, widely investigated, have proved their ability to act as a coagulant and/or flocculant, binding and improving sludge flocs, especially, the sludge flocculation, settling and dewatering. However, with regard to the most used sludge treatment methods in developing countries, extracellular polymeric substances (EPS), compounds that appear to be a key factor in sludge dewaterability are entirely missing in studies discussing the mechanisms of natural organic polymers sludge dewaterability. In advanced sludge treatment, EPS govern all the important mechanisms in sludge dewaterability. The aim of this review is to articulate a comparative study on the behavior of EPS during sludge conditioning and the dewatering improvement using natural coagulants while reviewing the interactions of natural organic conditioners with EPS.